Comparison of apparent diffusion coefficient and relative apparent diffusion coefficient values for differential diagnosis of breast lesions - Parlak, Ayşe Eda; Yağcı, Buket (The European Research Journal, 2022)
Objectives: The purpose the study was to evaluate the role of diffusion weighted magnetic resonance imaging (DW-MRI) in diagnosis of benign and malignant breast lesions, to calculate a cut-off apparent diffusion coefficient (ADC) value and to explore use of relative ADC (r ADC) for improving sensitivity and specificity of MRI in diagnosis of breast cancer. Methods: This retrospective study based on a cohort of patients who underwent dynamic contrast enhanced (DCE)-MRI having suspicious breast mass by ultrasonography and mammography to whom DWI sequence was added to the routine diagnostic MRI. ADC and r ADC (lesion/normal breast tissue) values of breast masses were calculated. The threshold ADC values used to differentiate benign and malignant lesions were determined using receiver operating characteristic analysis, sensitivity, specificity, positive predictive value and negative predictive value were calculated. Results: Malignant masses had significantly lower ADC (mean: 1.03 ± 0.36 × 10-3 mm2/s) and r ADC (mean: 0.66 ± 0.22 × 10-3 mm2/s) values than those of benign masses with ADC (mean: 1.50 ± 0.56 × 10−3 mm2/s) and r ADC (mean: 0.97 ± 0.31 × 10-3 mm2/s) values, respectively (p = 0.001 for both). The best cut-off value for the lesion ADC was 1.09 × 10-3 mm2/s with a sensitivity of 72.73%, and specificity of 79.17%. The best cut-off value for r ADC was 0.83 with sensitivity of 78.79% and specificity of 70.83%. Conclusions: DWI has high diagnostic value with high sensitivity and specificity differentiating benign and malignant breast lesions. ADC and r ADC values can improve the diagnostic accuracy of differentiating benign and malignant breast lesions.